Knowledge, attitudes, and behavior toward concussion in adult cyclists. (28th July 2020) - O'Reilly, Maureen; Mahon, Susan; Reid, Duncan; Hume, Patria; Hardaker, Natalie; Theadom, Alice
ABSTRACT: Objective: To determine knowledge, attitudes, and behavior toward concussion in cyclists and to identify predictors of concussion knowledge. Methods: Cycling organizations sent members a web link to online information about the study and a questionnaire. Anyone aged >16 years, living in New Zealand and engaged in a cycling activity was invited to participate. The 36-item questionnaire included sociodemographics, knowledge about concussion, helmet use, and personal concussion history. Data were collected between 15/05/19 and 30/06/19. A multiple linear regression model identified factors associated with levels of concussion knowledge. Results: The questionnaire was completed by 672 participants aged between 16 and 82 years (x̄ = 48.6 years). Knowledge of concussion was high. However, knowledge that helmets are not able to prevent concussion was low and time to return to sport after injury was variable. Knowledge did not always translate to seeking of medical attention or replacement of helmet behavior. Younger age and having sustained at least one prior concussion were associated with higher levels of concussion knowledge F(df = 3) = 8.81, p < .001. Conclusions: Knowledge and attitudes toward concussion were positive. However, knowledge gaps and discrepancies between attitudes and behavior were identified. Consistent, clear messages are needed around return to sport timeframes.